Production Model with ERP for optimum Productivity in SMEs of the Metal Mechanics Sector in Trujillo La Libertad (SCIÉNDO INGENIUM, 2026)
The objective of this research is to propose a technological solution that contributes to improving the competitiveness of micro and small enterprises in the metal-mechanical sector in the city of Trujillo, through greater integration with the supply chain by means of information and communication technologies. The study focuses on the implementation of an Enterprise Resource Planning (ERP) system as a strategic tool to optimize productivity, strengthen innovation capabilities, improve value chain management, and support business decision-making. The methodology is based on the design and development of an advanced production system, structured through functional ERP modules, as well as on the validation of the source code to ensure its proper operation. As a result, the first stage of the project was completed, corresponding to the design and integration of the system modules, which were implemented and hosted in the Data Center of the Department of Industrial Engineering at the National University of Trujillo. The proposed solution demonstrates a positive impact on productivity, profitability, and strategic management of the MSEs in the analyzed sector.
Keywords: ERP; competitiveness; ICT; supply chain; MSEs